Nitrided steel parts
A nitrided steel part with controlled V precipitates and specific core composition enhances bending fatigue strength by balancing surface and core hardness, addressing the limitations of existing nitriding treatments.
Patent Information
- Application Number
- JP2020207006
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-14
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2040-12-14
AI Technical Summary
Existing methods for increasing the bending fatigue strength of nitrided steel parts, such as those used in mechanical structural components, do not sufficiently enhance this property despite efforts to improve surface hardness through nitriding treatments.
A nitrided steel part with a specific chemical composition and microstructure is developed, featuring a nitrided layer and a core portion, where the core composition includes C: 0.03~0.25%, Si: 0.02~0.50%, Mn: 0.70~2.50%, P: 0.035% or less, S: 0.050% or less, Al: 0.005~0.050%, Cr: less than 0.03~0.30%, V: 0.10~0.40%, and N: 0.003~0.030%, with V precipitates controlled to satisfy the ratio [V in precipitates]/[V]≧0.30, and a diffusible hydrogen amount of 0.10 ppm or more, promoting plate-like V precipitates for enhanced resistance to dislocation movement.
The solution results in nitrided steel parts with significantly improved bending fatigue strength, suitable for applications requiring high resistance to bending and torsional stresses.
Smart Images

Figure 0007617376000003 
Figure 0007617376000001 
Figure 0007617376000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a nitrided steel part, and more particularly to a nitrided steel part which is formed by cold working and then subjected to a nitriding treatment. [Background technology]
[0002] Structural steel materials are used as materials for machine structural parts, such as automobile parts, construction machine parts, industrial machine parts, etc. Structural steel materials include, for example, carbon steel materials for machine structures, alloy steel materials for machine structures, etc.
[0003] In recent years, the weight and size of machine structural parts have been reduced in order to improve the fuel efficiency of automobiles, construction vehicles, industrial machinery, etc. The weight and size of machine structural parts increases the load on the machine structural parts. Therefore, machine structural parts manufactured using structural steel materials are required to have excellent bending fatigue strength. For example, machine structural parts with high tooth depth such as helical gears and worm gears are required to have high bending fatigue strength.
[0004] In order to manufacture machine structural parts having excellent bending fatigue strength using structural steel, a method of performing quenching and tempering treatment after hot forging is sometimes used. However, in the method of performing quenching and tempering treatment after hot forging, the shape accuracy during processing may be low. Therefore, in order to improve the shape accuracy during processing, a method of performing cold working may be used instead of the method of performing hot forging and quenching and tempering treatment after hot forging.
[0005] When cold working is performed, work hardening occurs due to the cold working, and the bending fatigue strength of the machine structural parts is improved. However, it is difficult to obtain a bending fatigue strength as high as that obtained by hot forging and quenching and tempering treatments after hot forging only by work hardening due to cold working. Therefore, as a method for increasing the bending fatigue strength when cold working is performed, a method for increasing the bending fatigue strength of the machine structural parts by performing age hardening treatment after cold working has been proposed.
[0006] A steel material that is used to manufacture machine structural parts by performing age hardening treatment after cold working is proposed, for example, in JP 2019-173168 A (Patent Document 1).
[0007] The cold forging steel material of Patent Document 1 consists, in mass%, of C: 0.02-0.25%, Si: 0.005-0.50%, Mn: over 0.70-2.50%, P: 0.035% or less, S: 0.050% or less, Al: 0.005-0.050%, Cr: 0.02-0.70%, V: 0.02-0.30%, N: 0.003-0.030%, Nb: 0-0.10%, B: 0-0.005%, Ca: 0-0.005%, Bi: 0-0.10%, Pb: 0-0.20%, and the balance: Fe and impurities. In the cold forging steel material of Patent Document 1, the total content of Cu, Ni, and Mo in the above impurities is 0.05 mass% or less, and the Ti content in the above impurities is 0.005 mass% or less, and the chemical composition satisfies formula (1). In addition, formula (1) is [V precipitates] / [V content]≦0.50. In the cold forging steel material of Patent Document 1, the microstructure contains ferrite, pearlite, and / or bainite. The area ratio of ferrite in the microstructure is 10 to 90%. Patent Document 1 describes that this provides high cold forgeability and high bending fatigue strength when subjected to age hardening treatment after cold forging.
[0008] However, even when age hardening is performed after cold working, the bending fatigue strength of the machine structural parts may not be sufficiently increased in some cases. Therefore, as a method for further increasing the bending fatigue strength, a method has been proposed in which nitriding is performed after cold working instead of age hardening.
[0009] A steel material that is used as a raw material for manufacturing machine structural parts by performing nitriding treatment after cold working is proposed, for example, in JP-A-9-279296 (Patent Document 2).
[0010] The nitrocarburizing steel of Patent Document 2 has a chemical composition containing, in mass%, C: 0.01-0.15%, Si: 0.01-1.00%, Mn: 0.1-1.5%, Cr: 0.1-2.0%, Al: more than 0.10% to 1.00%, V: 0.05-0.40%, with the balance being iron and unavoidable impurities, and the added amounts of Cr, Al, and V satisfy the following formula (1). The formula (1) is 1.65≦Cr+6.2Al+1.9V. This nitrocarburizing steel further has a core hardness of 200 or less in Hv after hot rolling or hot forging, and a limit compression ratio in the subsequent cold forging of 65% or more. Patent Document 2 states that the nitrocarburizing steel of Patent Document 2 has good cold forgeability and excellent nitrocarburizing characteristics with high surface hardness. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] JP 2019-173168 A [Patent Document 2] Japanese Patent Application Publication No. 9-279296 Summary of the Invention [Problem to be solved by the invention]
[0012] In Patent Document 2, the surface hardness of a nitrided steel part is increased by carrying out a nitriding treatment after cold forging. This is thought to improve the surface fatigue strength against pitting, etc. However, there are cases where the bending fatigue strength of a nitrided steel part is not sufficiently improved by simply increasing the surface hardness.
[0013] It is an object of the present disclosure to provide a nitrided steel component having high bending fatigue strength. [Means for solving the problem]
[0014] The nitrided steel part according to the invention has a nitrided layer on the surface layer of the nitrided steel part; A core portion located inside the nitride layer, The chemical composition of the core is, in mass%, C: 0.03-0.25%, Si: 0.02 to 0.50%, Mn: over 0.70~2.50%, P: 0.035% or less, S: 0.050% or less, Al: 0.005 to 0.050%, Cr: 0.03 to less than 0.30% V: over 0.10 to 0.40%, and N: 0.003 to 0.030%, the balance being Fe and impurities, When the V content in the chemical composition of the core portion is defined as [V] (mass%) and the total V content in the V precipitates of the core portion is defined as [V in precipitates] (mass%), formula (1) is satisfied, The amount of diffusible hydrogen when hydrogen is charged by the cathodic hydrogen charging method is 0.10 ppm or more. [V in precipitate] / [V]≧0.30 (1) Effect of the Invention
[0015] The nitrided steel parts according to the invention have high bending fatigue strength. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a plan view of an Ono-type rotary bending test piece prepared in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present inventors conducted various investigations to solve the above-mentioned problems and obtained the following findings.
[0018] First, the present inventors determined that the core portion contains, in mass%, C: 0.03 to 0.25%, Si: 0.02 to 0.50%, Mn: more than 0.70 to 2.50%, P: 0.035% or less, S: 0.050% or less, Al: 0.005 to 0.050%, Cr: 0.03 to less than 0.30%, V: more than 0.10 to 0.40%, N: 0.003 to 0.030%, Nb: 0 to 0.100%, B: 0. A method was investigated for increasing the surface hardness and improving the bending fatigue strength of a nitrided steel part having a chemical composition of Cu: 0.0100%, Cu: 0-0.20%, Ni: 0-0.20%, Ca: 0-0.0050%, Bi: 0-0.100%, Pb: 0-0.090%, Mo: 0-0.05%, Ti: 0-0.005%, and the balance being Fe and impurities, by nitriding treatment. However, there were cases where the bending fatigue strength was not increased by merely increasing the surface hardness of the nitrided steel part.
[0019] Therefore, the present inventors investigated the reason why the bending fatigue strength of a nitrided steel part does not increase only by increasing the hardness of the surface. Nitrided steel parts are mainly used in parts that are subjected to bending stress and torsional stress. The bending stress and torsional stress that a nitrided steel part receives are maximum at the surface of the nitrided steel part. Therefore, the origin of fatigue fracture is likely to occur on the surface of the nitrided steel part. Therefore, by increasing the hardness of the surface, fracture originating from the surface is suppressed. On the other hand, although the above stress decreases toward the core of the nitrided steel part, a certain amount of load is also applied to the core of the nitrided steel part. Therefore, in a nitrided steel part that is subjected to bending stress or torsional stress, fatigue fracture may occur originating from the core of the nitrided steel part. Therefore, it is effective to not only increase the hardness of the surface but also to increase the hardness of the core.
[0020] Next, the inventors investigated the reason why the hardness of the core of a nitrided steel part is not sufficiently increased by nitriding. By carrying out nitriding on a steel material after cold working, the steel material becomes a nitrided steel part having a nitrided layer at the surface layer and a core part deeper than the nitrided layer. Here, the nitrided layer is a layer formed on the surface layer of the steel material by nitriding, and has a higher hardness than the core part.
[0021] In the nitriding process, nitrogen is diffused and penetrated from the surface of the steel material, and nitrides such as Cr nitrides, Al nitrides, and V nitrides are formed in the surface layer of the steel material. Therefore, if the content of elements that easily form nitrides such as Cr, Al, and V (hereinafter also referred to as nitride-forming elements) in the steel material is high, the formation of nitrides in the surface layer of the steel material is promoted. Therefore, the hardness of the nitrided layer is increased. Therefore, in order to increase the hardness of the surface of the nitrided steel part, it is sufficient to contain a large amount of nitride-forming elements in the steel material that is the material of the nitrided steel part. However, in this case, most of the nitrogen supplied from the surface of the steel material is used to form Cr nitrides, Al nitrides, V nitrides, and the like. Therefore, there are cases where nitrogen is not sufficiently diffused to the inside of the steel material. In this case, the hardness of the core of the nitrided steel part is not sufficiently increased, and the bending fatigue strength of the nitrided steel part is not sufficiently increased. If the nitriding process is performed on a steel material that contains a large amount of Cr, Al, V, and the like to increase the hardness of the core of the nitrided steel part, the hardness of the nitrided layer of the nitrided steel part will be significantly increased. However, if the hardness of the nitrided layer is excessively high, the bending fatigue strength is reduced. Therefore, the inventors of the present invention have considered that it is better to increase the hardness of the core of the nitrided steel part without excessively increasing the hardness of the nitrided layer, thereby increasing the bending fatigue strength of the nitrided steel part.
[0022] As a result of further research and consideration, the inventors have concluded that by utilizing precipitation strengthening by V precipitates in addition to nitriding treatment, it is possible to increase the hardness of the core of a nitrided steel part without excessively increasing the hardness of the nitrided layer, and thereby to increase the bending fatigue strength of the nitrided steel part.
[0023] Specifically, in precipitation strengthening by V precipitates, a large number of fine nano-sized V precipitates are generated to increase bending fatigue strength. In this specification, V carbonitride (V(C,N)), V carbide (VC) and V nitride (VN) are collectively defined as "V precipitates". Most of the V precipitates precipitated in nitrided steel parts are V carbonitride (V(C,N)). However, some of the V precipitates may precipitate as V carbide (VC) and / or V nitride (VN). V carbide and V nitride are considered to have the same effect as V carbonitride. Therefore, in this specification, "V precipitates" includes V carbonitride, V carbide and V nitride.
[0024] Specifically, the V content in the chemical composition of the core of a nitrided steel part is defined as [V] (mass%), and the total V content in V precipitates in the core of a nitrided steel part when the chemical composition of the core of the nitrided steel part is taken as 100% is defined as [V in precipitates] (mass%). In this case, in a nitrided steel part in which the content of each element in the chemical composition of the core is within the above-mentioned range, if the following formula (1) is satisfied, a sufficient amount of V precipitates is precipitated in the nitrided steel part to increase bending fatigue strength. [V in precipitate] / [V]≧0.30 (1)
[0025] As described above, in a nitrided steel part in which the content of each element in the chemical composition of the core is within the above-mentioned range, if a sufficient amount of V precipitates is precipitated to satisfy formula (1), the bending fatigue strength of the nitrided steel part is improved to a certain extent. However, in a nitrided steel part in which the content of each element in the chemical composition of the core is within the above-mentioned range, even if a sufficient amount of V precipitates is precipitated to satisfy formula (1), the bending fatigue strength may be insufficient when used in a gear with a high tooth height. Therefore, the present inventors have investigated conditions under which even higher bending fatigue strength can be obtained. As a result, they have considered that controlling the shape of the V precipitates is effective in further increasing the bending fatigue strength of the nitrided steel part by precipitation strengthening due to the V precipitates. This point will be explained below.
[0026] There are spherical V precipitates and plate-shaped V precipitates. In the following explanation, spherical V precipitates will be referred to as spherical V precipitates, and plate-shaped V precipitates will be referred to as plate-shaped V precipitates. When spherical V precipitates form, the interface between the spherical V precipitates and the parent phase is mainly an incoherent interface. Spherical V precipitates that precipitate as incoherent interfaces act only as simple obstacles, hindering only the motion of dislocations that directly collide with them. For this reason, spherical V precipitates do not provide much resistance to dislocation motion.
[0027] On the other hand, the plate-like V precipitates have a NaCl-type crystal structure and have a Baker-Nutting (BN) relationship with the parent phase (α) (i.e., the {100} of the plate-like V precipitates is parallel to the {100} of the parent phase, and the plate-like V precipitates <100> Orientation and parent phase <110> A coherent or semi-coherent interface is formed in which the lattice direction is parallel to the lattice direction. The coherent or semi-coherent interface forms a coherent strain field around the plate-shaped V precipitate. This coherent strain field interacts with dislocations, inhibiting not only dislocation motion that directly impinges, but also dislocation motion that passes near the plate-shaped V precipitate. For this reason, the plate-shaped V precipitate provides a large resistance to dislocation motion.
[0028] Based on the above results of the study, the inventors believed that by precipitating as many plate-shaped V precipitates as possible in the core of a nitrided steel part, rather than spherical V precipitates, it would be possible to further increase resistance to dislocation motion, and thereby obtain high bending fatigue strength in the nitrided steel part.
[0029] However, the size of the plate-shaped V precipitates is at the nano level. Therefore, it is extremely difficult to identify the plate-shaped V precipitates and the spherical V precipitates by microstructural observation and to determine the proportion of the plate-shaped V precipitates in the V precipitates. On the other hand, hydrogen is easily trapped at the coherent interface and the semi-coherent interface, and is not easily trapped at the incoherent interface. In other words, the plate-shaped V precipitates are easy to trap hydrogen, and the spherical V precipitates are not easy to trap hydrogen. Therefore, in a nitrided steel part in which V precipitates are precipitated in an amount that satisfies formula (1), if the amount of hydrogen trapping is large when hydrogen is charged, it means that the proportion of the plate-shaped V precipitates is high among the amount of V precipitates that increases bending fatigue strength.
[0030] Therefore, the inventors investigated the relationship between the amount of diffusible hydrogen obtained when hydrogen is charged into the core of a nitrided steel part by the cathodic hydrogen charging method described below as an index showing the proportion of plate-like V precipitates in the V precipitates, and fatigue properties. As a result, they found that in the core of a nitrided steel part in which the content of each element in the chemical composition of the core is within the above-mentioned range and the amount of V precipitates satisfying formula (1), if the amount of diffusible hydrogen is 0.10 ppm or more when hydrogen is charged by the cathodic hydrogen charging method, the proportion of plate-like V precipitates in the V precipitates is high, and excellent bending fatigue strength can be obtained.
[0031] The nitrided steel part according to this embodiment, which was completed based on the above findings, has the following features.
[0032] [1] 1. A nitrided steel part, comprising: a nitrided layer on the surface layer of the nitrided steel part; A core portion located inside the nitride layer, The chemical composition of the core is, in mass%, C: 0.03-0.25%, Si: 0.02 to 0.50%, Mn: over 0.70~2.50%, P: 0.035% or less, S: 0.050% or less, Al: 0.005 to 0.050%, Cr: 0.03 to less than 0.30% V: over 0.10 to 0.40%, and N: 0.003 to 0.030%, the balance being Fe and impurities, When the V content in the chemical composition of the core portion is defined as [V] (mass%) and the total V content in the V precipitates of the core portion is defined as [V in precipitates] (mass%), formula (1) is satisfied, The amount of diffusible hydrogen when hydrogen is charged using the cathodic hydrogen charging method is 0.10 ppm or more. Nitrided steel parts. [V in precipitate] / [V]≧0.30 (1)
[0033] [2] A nitrided steel part according to [1], The chemical composition of the core portion further includes, instead of a part of Fe, Nb: 0.100% or less, and B: 0.0100% or less, Contains one or more selected from the group consisting of Nitrided steel parts.
[0034] [3] A nitriding steel part according to [1] or [2], The chemical composition of the core portion further includes, instead of a part of Fe, Cu: 0.20% or less, and Ni: 0.20% or less, Contains one or more selected from the group consisting of Nitrided steel parts.
[0035] [4] A nitriding steel part according to any one of [1] to [3], The chemical composition of the core portion further includes, instead of a part of Fe, Ca: 0.0050% or less, Bi: 0.100% or less, and Pb: 0.090% or less, Contains one or more selected from the group consisting of Nitrided steel parts.
[0036] [5] A nitriding steel part according to any one of [1] to [4], The chemical composition of the core portion further includes, instead of a part of Fe, Mo: 0.05% or less, and Ti: 0.005% or less, Contains one or more selected from the group consisting of Nitrided steel parts.
[0037] The nitrided steel component according to the present embodiment has high bending fatigue strength.
[0038] The nitrided steel part according to this embodiment will be described in detail below. "%" for elements means mass %.
[0039] [Composition of nitriding steel parts] The nitrided steel part of this embodiment includes a nitrided layer and a core. The nitrided layer is formed on the surface layer of the nitrided steel part. The nitrided layer has a higher hardness than the core. The nitrided layer and the core in the nitrided steel part can be distinguished by N concentration distribution measurement using, for example, an EPMA (Electron Probe Micro Analyzer).
[0040] [Chemical composition] The chemical composition of the core of the nitrided steel part according to this embodiment contains the following elements:
[0041] C: 0.03 to 0.25% Carbon (C) combines with V in the nitrided steel part to form V precipitates. When V precipitates are formed, the bending fatigue strength of the nitrided steel part is increased by precipitation strengthening. C also increases the area ratio of pearlite and bainite in the nitrided steel part. Pearlite and bainite are phases with higher strength than ferrite. Therefore, when the area ratio of pearlite and bainite increases, the bending fatigue strength of the nitrided steel part is increased. If the C content is less than 0.03%, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the C content exceeds 0.25%, the cold workability of the steel material that is the material of the nitrided steel part is reduced even if the contents of other elements are within the range of this embodiment. Therefore, the C content is 0.03 to 0.25%. The preferable lower limit of the C content is 0.05%, more preferably 0.07%, and more preferably 0.10%. The preferable upper limit of the C content is less than 0.23%, more preferably 0.21%, and more preferably 0.19%.
[0042] Silicon: 0.02 to 0.50% Silicon (Si) increases the bending fatigue strength of nitrided steel parts. In addition, Si deoxidizes steel. If the Si content is less than 0.02%, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Si content exceeds 0.50%, the cold workability of the steel material that is the material of the nitrided steel parts decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Si content is 0.02 to 0.50%. The preferred lower limit of the Si content is 0.05%, more preferably 0.07, and even more preferably 0.10%. The preferred upper limit of the Si content is 0.45%, more preferably 0.40%, and even more preferably 0.35%.
[0043] Mn: over 0.70~2.50% Manganese (Mn) promotes the formation of pearlite or bainite, which are high strength phases. As a result, it increases the bending fatigue strength of the nitrided steel part. If the Mn content is 0.70% or less, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Mn content exceeds 2.50%, the strength of the steel material, which is the raw material of the nitrided steel part, becomes too high, and the cold workability decreases, even if the contents of other elements are within the range of this embodiment. If the Mn content exceeds 2.50%, pearlite and bainite are generated excessively in the raw material steel material, and the ferrite area ratio decreases excessively. Therefore, the cold workability further decreases. Therefore, the Mn content is more than 0.70 to 2.50%. The preferable lower limit of the Mn content is 0.75%, more preferably 0.80%, more preferably 1.20%, and more preferably 1.40%. The preferable upper limit of the Mn content is 2.30%, more preferably 2.10%, and more preferably 1.90%.
[0044] P:0.035% or less Phosphorus (P) is an impurity. P segregates at grain boundaries and reduces the bending fatigue strength of nitrided steel parts. Therefore, the P content is 0.035% or less. A preferred upper limit of the P content is 0.030%, more preferably 0.025%, and even more preferably 0.020%. It is preferable that the P content is as low as possible. However, excessive reduction of the P content increases the manufacturing cost. Therefore, in consideration of normal industrial production, a preferred lower limit of the P content is more than 0%, more preferably 0.001%, more preferably 0.005%, and even more preferably 0.010%.
[0045] S: 0.050% or less Sulfur (S) is an impurity. S combines with Mn to form MnS, which improves the machinability of steel. However, if the S content exceeds 0.050%, coarse MnS is generated. Coarse MnS is likely to become the starting point of cracks during cold working. Therefore, the cold workability of steel, which is the material for nitrided steel parts, decreases. Therefore, the S content is 0.050% or less. The preferred upper limit of the S content is 0.045%, more preferably 0.040%, more preferably 0.030%, and even more preferably 0.020%. Excessive reduction of the S content increases the manufacturing cost. Therefore, considering normal industrial production, the preferred lower limit of the S content is more than 0%, more preferably 0.001%, more preferably 0.005%, and even more preferably 0.006%.
[0046] Al: 0.005 to 0.050% Aluminum (Al) deoxidizes steel. It also forms Al nitrides and increases the hardness of the nitrided layer. If the Al content is less than 0.005%, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Al content exceeds 0.050%, coarse Al-based inclusions such as Al oxides are generated in the steel material even if the contents of other elements are within the range of this embodiment, and the coarse Al-based inclusions are likely to become the starting point of cracks during cold working. It also reduces the nitrided layer depth, and the bending fatigue strength of the nitrided steel part is reduced. Therefore, the Al content is 0.005 to 0.050%. The preferred lower limit of the Al content is 0.005%, more preferably 0.010%, and more preferably 0.015%. The preferred upper limit of the Al content is 0.045%, more preferably 0.040%, more preferably 0.030%, and more preferably 0.020%. In the nitrided steel part of this embodiment, the Al content means the total Al content.
[0047] Cr: 0.03 to less than 0.30% Chromium (Cr) increases the bending fatigue strength of nitrided steel parts. Cr also forms Cr nitrides by nitriding, increasing the hardness of the nitrided layer. If the Cr content is less than 0.03%, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Cr content is 0.30% or more, the depth of the nitrided layer decreases and the bending fatigue strength of the nitrided steel parts decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Cr content is 0.03 to less than 0.30%. The preferred lower limit of the Cr content is 0.05%, more preferably 0.07%, and even more preferably 0.10%. The preferred upper limit of the Cr content is 0.28%, more preferably 0.25%, and even more preferably 0.20%.
[0048] V: More than 0.10~0.40% Vanadium (V) combines with C and / or N in the steel material in the core of the nitrided steel part to form V precipitates. If V precipitates are formed in the core, the bending fatigue strength of the nitrided steel part is increased by precipitation strengthening. V also forms V nitrides by nitriding treatment to increase the hardness of the nitrided layer. If the V content is 0.10% or less, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the V content exceeds 0.40%, the V precipitates are likely to become spheroidal even if the contents of other elements are within the range of this embodiment. Therefore, the bending fatigue strength of the nitrided steel part is reduced. If the V content exceeds 0.40%, the cold workability of the steel material that is the material of the nitrided steel part is further reduced. Therefore, the V content is more than 0.10 to 0.40%. The preferable lower limit of the V content is 0.12%, more preferably 0.15%, and even more preferably 0.18%. The upper limit of the V content is preferably 0.38%, more preferably 0.35%, further preferably 0.30%, and further preferably 0.28%.
[0049] N: 0.003 to 0.030% Nitrogen (N) combines with V in the steel material to form V precipitates. If V precipitates are formed, the bending fatigue strength of the nitrided steel part is increased by precipitation strengthening. If the N content is less than 0.003%, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the N content exceeds 0.030%, V nitrides (VN), which are V precipitates, are excessively precipitated in the steel material after hot working even if the contents of other elements are within the range of this embodiment. If V nitrides are excessively precipitated, the V nitrides are likely to be spheroidized in the nitriding process described later. Alternatively, if V nitrides are excessively precipitated during cooling after hot working, the V source for the V precipitates to be precipitated in the core portion in the nitriding process described later decreases. Therefore, it becomes impossible to sufficiently precipitate plate-shaped V precipitates in the core portion in the nitriding process. As a result, the bending fatigue strength decreases. Therefore, the N content is 0.003 to 0.030%. The lower limit of the N content is preferably more than 0.003%, more preferably 0.004%, and even more preferably 0.005%. The upper limit of the N content is preferably 0.025%, more preferably 0.020%, and even more preferably 0.015%.
[0050] [About optional elements] The chemical composition of the core of the nitrided steel part may contain, in place of a portion of Fe, one or more elements selected from the group consisting of 0.100% or less Nb and 0.0100% or less B. These elements are optional elements, and all of them increase the bending fatigue strength of the nitrided steel part.
[0051] Nb: 0.100% or less Niobium (Nb) is an optional element and may not be contained. That is, the Nb content may be 0%. When it is contained, that is, when the Nb content is more than 0%, Nb combines with C and / or N in the steel material to form Nb precipitates. If Nb precipitates are formed, the bending fatigue strength of the nitrided steel part is increased by precipitation strengthening. Therefore, even if even a small amount of Nb is contained, the above effect can be obtained to a certain extent. However, if the Nb content exceeds 0.100%, the cold workability of the steel material, which is the material of the nitrided steel part, decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Nb content is 0 to 0.100%. When Nb is contained, the Nb content is 0.100% or less. The preferable lower limit of the Nb content is more than 0%, more preferably 0.001%, more preferably 0.010%, and even more preferably 0.020%. The upper limit of the Nb content is preferably 0.080%, more preferably 0.070%, and further preferably 0.060%.
[0052] B: 0.0100% or less Boron (B) is an optional element and may not be contained. That is, the B content may be 0%. When it is contained, that is, when the B content is more than 0%, B strengthens the grain boundaries of the nitrided steel part and increases the bending fatigue strength of the nitrided steel part. Therefore, even if even a small amount of B is contained, the above effect can be obtained to a certain extent. However, when the B content exceeds 0.0100%, the above effect is saturated. When the B content exceeds 0.0100%, the raw material cost further increases and the manufacturability also decreases. Therefore, the B content is 0 to 0.0100%. When B is contained, the B content is 0.0100% or less. The preferable lower limit of the B content is more than 0%, more preferably 0.0001%, more preferably 0.0010%, more preferably 0.0020%, and more preferably 0.0050%. The upper limit of the B content is preferably 0.0080%, more preferably 0.0070%, and further preferably 0.0060%.
[0053] The chemical composition of the core of the nitrided steel part may contain one or more elements selected from the group consisting of Cu: 0.20% or less and Ni: 0.20% or less, instead of a portion of Fe. These elements are optional elements, and all of them increase the bending fatigue strength of the nitrided steel part.
[0054] Cu:0.20% or less Copper (Cu) is an optional element and may not be contained. That is, the Cu content may be 0%. When it is contained, that is, when the Cu content is more than 0%, Cu improves the hardenability of the steel material and increases the bending fatigue strength of the nitrided steel part. If even a small amount of Cu is contained, the above effect can be obtained to a certain extent. However, if the Cu content exceeds 0.20%, the cold workability of the steel material, which is the material of the nitrided steel part, may decrease even if the contents of other elements are within the range of this embodiment. Therefore, the Cu content is 0 to 0.20%. When Cu is contained, the Cu content is 0.20% or less. The preferred lower limit of the Cu content is more than 0%, more preferably 0.01%, more preferably 0.05%, and more preferably 0.10%. The preferred upper limit of the Cu content is 0.19%, more preferably 0.18%, and more preferably 0.15%.
[0055] Ni: 0.20% or less Nickel (Ni) is an optional element and may not be contained. In other words, the Ni content may be 0%. When it is contained, that is, when the Ni content is more than 0%, Ni improves the hardenability of the steel material and increases the bending fatigue strength of the nitrided steel part. If even a small amount of Ni is contained, the above effects can be obtained to a certain extent. However, if the Ni content exceeds 0.20%, the cold workability of the steel material that is the material of the nitrided steel part may decrease even if the contents of other elements are within the range of this embodiment. Therefore, the Ni content is 0 to 0.20%. When Ni is contained, the Ni content is 0.20% or less. The preferred lower limit of the Ni content is more than 0%, more preferably 0.01%, more preferably 0.05%, and more preferably 0.10%. The preferred upper limit of the Ni content is 0.19%, more preferably 0.18%, and more preferably 0.15%.
[0056] The chemical composition of the core of the nitrided steel part may contain, in place of a portion of Fe, one or more elements selected from the group consisting of Ca: 0.0050% or less, Bi: 0.100% or less, and Pb: 0.090% or less. These elements are optional elements, and all of them improve the machinability of the nitrided steel part before nitriding treatment.
[0057] Ca:0.0050% or less Calcium (Ca) is an optional element and may not be contained. In other words, the Ca content may be 0%. When it is contained, that is, when the Ca content is more than 0%, Ca enhances the machinability of the nitrided steel part. If even a small amount of Ca is contained, the above effect can be obtained to some extent. However, when the Ca content exceeds 0.0050%, even if the contents of other elements are within the range of this embodiment, the cold workability of the steel material that is the material of the nitrided steel part may be reduced due to coarse precipitates such as CaO. Therefore, the Ca content is 0 to 0.0050%. When Ca is contained, the Ca content is 0.0050% or less. The preferred lower limit of the Ca content is more than 0%, more preferably 0.0001%, more preferably 0.0010%, and more preferably 0.0020%. The preferred upper limit of the Ca content is 0.0045%, more preferably 0.0043%, and more preferably 0.0040%.
[0058] Bi:0.100% or less Bismuth (Bi) is an optional element and may not be contained. In other words, the Bi content may be 0%. When it is contained, that is, when the Bi content is more than 0%, Bi enhances the machinability of the nitrided steel part. If even a small amount of Bi is contained, the above effect can be obtained to a certain extent. However, if the Bi content exceeds 0.100%, the cold workability of the steel material that is the material of the nitrided steel part may decrease even if the contents of other elements are within the range of this embodiment. Therefore, the Bi content is 0 to 0.100%. When Bi is contained, the Bi content is 0.100% or less. The preferred lower limit of the Bi content is more than 0%, more preferably 0.001%, more preferably 0.010%, more preferably 0.020%, and more preferably 0.030%. The preferred upper limit of the Bi content is 0.080%, more preferably 0.070%, and more preferably 0.060%.
[0059] Pb:0.090% or less Lead (Pb) is an optional element and may not be contained. In other words, the Pb content may be 0%. When it is contained, that is, when the Pb content is more than 0%, Pb enhances the machinability of the nitrided steel part. If even a small amount of Pb is contained, the above effect can be obtained to some extent. However, if the Pb content exceeds 0.090%, the cold workability of the steel material that is the material of the nitrided steel part may decrease even if the contents of other elements are within the range of this embodiment. Therefore, the Pb content is 0 to 0.090%. When Pb is contained, the Pb content is 0.090% or less. The preferred lower limit of the Pb content is more than 0%, more preferably 0.001%, more preferably 0.010%, more preferably 0.020%, and more preferably 0.040%. The preferred upper limit of the Pb content is 0.080%, more preferably 0.075%, and more preferably 0.070%.
[0060] The chemical composition of the core of the nitrided steel part may contain one or more elements selected from the group consisting of Mo: 0.05% or less and Ti: 0.005% or less, instead of a portion of Fe. As long as the contents of these elements are within the above-mentioned ranges, the effects of the nitrided steel part according to this embodiment can be obtained.
[0061] Mo: 0.05% or less Molybdenum (Mo) is an impurity and may not be contained. In other words, the Mo content may be 0%. Mo reduces the cold workability of the steel material that is the raw material of the nitrided steel part. If the Mo content exceeds 0.05%, the cold workability is significantly reduced even if the contents of other elements are within the range of this embodiment. Therefore, the Mo content is 0.05% or less. Since the Mo content may be 0%, the Mo content is 0 to 0.05%. The preferred upper limit of the Mo content is 0.04%, and more preferably 0.03%. As described above, it is preferable that the Mo content is as low as possible. However, excessive reduction of the Mo content increases the manufacturing cost. Therefore, the preferred lower limit of the Mo content is 0.01%, and more preferably 0.02%.
[0062] Ti: 0.005% or less Titanium (Ti) is an impurity and may not be contained. That is, the Ti content may be 0%. Ti combines with N in the steel material of the nitrided steel part to form Ti-based inclusions such as TiN. The Ti-based inclusions are coarse and hard inclusions. Therefore, the Ti-based inclusions are likely to become the starting point of cracks during cold working. That is, the Ti-based inclusions reduce the cold workability of the steel material that is the material of the nitrided steel part. If the Ti content exceeds 0.005%, the cold workability is significantly reduced even if the contents of other elements are within the range of this embodiment. Therefore, the Ti content is 0.005% or less. Since the Ti content may be 0%, the Ti content is 0 to 0.005%. The preferred upper limit of the Ti content is 0.004%, and more preferably 0.003%. As described above, it is preferable that the Ti content is as low as possible. However, excessive reduction of the Ti content increases the manufacturing cost. Therefore, the lower limit of the Ti content is preferably 0.001%, and more preferably 0.002%.
[0063] [Microstructure of the core of nitrided steel parts] The microstructure of the core of the nitrided steel part of this embodiment contains ferrite, pearlite and / or bainite. In this specification, bainite includes martensite. In the microstructure observation described below, it is extremely difficult to distinguish between bainite and martensite after nitriding treatment. Therefore, in this specification, bainite and martensite are not distinguished from each other and are collectively referred to as "bainite".
[0064] More specifically, in the microstructure of the core of the nitrided steel part, the area ratio of ferrite is 20-90%. If the area ratio of ferrite is 20-90%, a nitrided steel part having high bending fatigue strength can be obtained. The area ratio of ferrite to obtain this effect is 20-90%. The preferred lower limit of the ferrite area ratio in the microstructure is 25%, more preferably 30%, and even more preferably 35%. The preferred upper limit of the ferrite area ratio is 80%, more preferably 75%, and even more preferably 70%.
[0065] In the microstructure of the core of the nitrided steel part, the area ratio of pearlite and / or bainite is preferably 10 to 80%, more preferably more than 5 to 50%, and even more preferably more than 5 to 80%.
[0066] [Method of identifying the structure and measuring the area ratio] The area ratio of ferrite and the total area ratio of pearlite and bainite in the structure of a nitrided steel part are measured by the following method.
[0067] The L-section of the nitrided steel part (a section parallel to the direction of progress in the drawing process of the cold working process described later) is used as the observation surface. The observation surface is mirror-polished and corroded with 3% nital (ethanol + 3% nitric acid solution). Of the corroded observation surface, a position 1 mm or more inward from the surface of the nitrided steel part is observed with an optical microscope. For example, if the nitrided steel part is cylindrical, the R / 2 position (the center position of radius R) of the above observation surface of the nitrided steel part may be observed with an optical microscope. The position 1 mm or more inward from the surface of the nitrided steel part corresponds to the core part inside the nitrided layer. The observation magnification is 400 times, and the observation field is 5 fields. The area ratio (%) of pro-eutectoid ferrite and the total area ratio (%) of pearlite and bainite are obtained for each field. The average value of the 5 fields is calculated for each structure, and is used as the ferrite area ratio (%) and the total area ratio (%) of pearlite and bainite of the nitrided steel part.
[0068] [Regarding formula (1)] The nitrided steel part of this embodiment having the above-mentioned chemical composition of the core further satisfies formula (1) when the V in the chemical composition of the core is defined as [V] (mass %) and the total V content in the V precipitates of the core is defined as [V in precipitates] (mass %). [V in precipitate] / [V]≧0.30 (1)
[0069] If [V in precipitates] / [V] is 0.30 or more, V precipitates are sufficiently precipitated in the core of the nitrided steel part. Therefore, the bending fatigue strength of the nitrided steel part is increased by precipitation strengthening of the core by V precipitates. On the other hand, if [V in precipitates] / [V] is less than 0.30, the above-mentioned effect cannot be sufficiently obtained. Therefore, [V in precipitates] / [V] is 0.30 or more. The preferable lower limit of [V in precipitates] / [V] is 0.31, and more preferably 0.32. The upper limit of [V in precipitates] / [V] is not particularly limited, but the preferable upper limit is 0.60, more preferably 0.55, and even more preferably 0.52.
[0070] [Method for measuring the total V content in V precipitates ([V in precipitates])] [V in precipitates] is determined by the following extraction residue analysis method. 3 Cut out a sample (approximately 7.8 g) and use it as a sample for the extraction residue. Electrolyze the sample at a constant current in a 10% AA system (a liquid mixture of tetramethylammonium chloride, acetylacetone, and methanol in a ratio of 1:10:100).
[0071] More specifically, first, the sample for extraction residue is subjected to preliminary electrolysis. This removes any adhering matter on the surface of the sample for extraction residue. The conditions for preliminary electrolysis are current: 1000 mA, time: 28 minutes, and room temperature (25°C). Then, the sample for extraction residue is subjected to ultrasonic cleaning in alcohol. This removes any adhering matter on the surface of the sample for extraction residue. The mass of the sample for extraction residue from which the adhering matter has been removed (mass of the sample for extraction residue before electrolysis) is measured.
[0072] Next, electrolysis is performed on the sample for extraction residue. The conditions for electrolysis are current: 173 mA, time: 142 minutes, and room temperature (25°C). The electrolyzed sample for extraction residue is removed. The removed sample for extraction residue is subjected to ultrasonic cleaning in alcohol. This removes any deposits (residue) on the surface of the sample for extraction residue. The solution after electrolysis and the solution used for ultrasonic cleaning are suction filtered using a filter. The mesh size of the filter is 0.2 μm. This allows the residue to be collected.
[0073] The mass of the sample for extraction residue from which the deposits (residue) have been removed (the mass of the sample for extraction residue after electrolysis) is measured. The "mass of the electrolyzed sample for extraction residue" is then calculated from the difference between the measured masses of the sample for extraction residue before and after electrolysis.
[0074] The residue collected on the filter is transferred to a petri dish and dried. The mass of the dried residue is measured. The residue is then analyzed using an ICP optical emission spectrometer (inductively coupled plasma optical emission spectrometer) in accordance with JIS G1258 (2014) to determine the "mass of V in the residue."
[0075] The "mass of V in the residue" thus determined is divided by the "mass of the electrolyzed sample for extraction residue" and expressed as a percentage, which is defined as [V in precipitates] (mass%). In other words, [V in precipitates] / [V] on the left side of formula (1) is the ratio of the total amount of V detected as V precipitates by the extraction residue analysis method to the amount of V in the chemical composition of the core of the nitriding steel part.
[0076] [About diffusible hydrogen content] The nitrided steel part of this embodiment having the above-mentioned chemical composition in the core further has a diffusible hydrogen amount of 0.10 ppm or more when hydrogen is charged by a cathodic hydrogen charging method. More specifically, the core of the nitrided steel part of this embodiment has a diffusible hydrogen amount of 0.10 ppm or more when hydrogen is charged by a cathodic hydrogen charging method in a 3% NaCl-3 g / LNH4SCN aqueous solution at a current density of 0.1 mA / cm 2 The amount of diffusible hydrogen is 0.10 ppm or more when hydrogen is charged by a cathodic hydrogen charging method with a current application time of 72 hours.
[0077] Hydrogen is easily trapped at the coherent and semi-coherent interfaces between the plate-shaped V precipitates and the parent phase, but is not easily trapped at the incoherent interfaces. In other words, plate-shaped V precipitates are easy to trap hydrogen, while spherical V precipitates are not. Therefore, if the amount of hydrogen trapped is large when hydrogen is charged in the core of a nitrided steel part in which V precipitates in an amount that satisfies formula (1) is precipitated, this means that the proportion of plate-shaped V precipitates is high among the amount of V precipitates that increases bending fatigue strength.
[0078] If the amount of diffusible hydrogen in the core of the nitrided steel part according to this embodiment is 0.10 ppm or more, the precipitation ratio of plate-shaped V precipitates is sufficiently increased. Therefore, precipitation strengthening occurs due to the plate-shaped V precipitates, and the bending fatigue strength of the nitrided steel part is increased. On the other hand, if the amount of diffusible hydrogen is less than 0.10 ppm, the above effect cannot be sufficiently obtained. Therefore, the amount of diffusible hydrogen in the core of the nitrided steel part according to this embodiment is 0.10 ppm or more. A preferable lower limit of the amount of diffusible hydrogen is 0.12 ppm. A preferable upper limit of the amount of diffusible hydrogen is not particularly limited, but is, for example, 0.50 ppm, more preferably 0.40 ppm, and even more preferably 0.30 ppm.
[0079] [Method for measuring diffusible hydrogen content] The method for measuring the amount of diffusible hydrogen is as follows. First, a test piece for measuring the amount of diffusible hydrogen is prepared. A round bar with a diameter of 7 mm and a length of 40 mm is cut out from the core of a nitrided steel part manufactured by the method described below. Specifically, for example, the round bar is cut out from a position 1 mm or more inward from the surface of the nitrided steel part (i.e., from the core). The cut out round bar is used as the test piece for measuring the amount of diffusible hydrogen. Hydrogen is introduced into the prepared test piece for measuring the amount of diffusible hydrogen by using a cathodic hydrogen charging method. Specifically, the test piece for measuring the amount of diffusible hydrogen is immersed in a 3% NaCl-3g / LNH4SCN aqueous solution, and a current density of 0.1 mA / cm is applied. 2Hydrogen is introduced into the test piece for measuring the amount of diffusible hydrogen by a cathodic hydrogen charging method under the conditions of a current flow rate of 72 hours and a current flow time of 72 hours. The timing at which the current flow is stopped is the timing at which the introduction of hydrogen into the test piece for measuring the amount of diffusible hydrogen is completed. After the introduction of hydrogen into the test piece for measuring the amount of diffusible hydrogen is completed, the time until the start of the temperature rise in the next temperature rise desorption gas chromatography (the time until the measurement of the amount of diffusible hydrogen) is preferably 30 minutes or less. If the time until the measurement of the amount of diffusible hydrogen exceeds 30 minutes after the introduction of hydrogen into the test piece for measuring the amount of diffusible hydrogen is completed, the test piece may be stored in a manner that can suppress the diffusion and release of hydrogen. The storage method is, for example, a method of immersing in liquid nitrogen.
[0080] After hydrogen is introduced into the test piece for measuring the amount of diffusible hydrogen, the amount of hydrogen in the test piece for measuring the amount of diffusible hydrogen is measured using thermal desorption gas chromatography. Specifically, the test piece is heated from room temperature to 400°C at a heating rate of 100°C / hour. The amount of hydrogen generated by the heating is measured at 5-minute intervals. A hydrogen release curve is obtained based on the amount of hydrogen obtained. The cumulative amount of hydrogen released from room temperature to 350°C is calculated from the hydrogen release curve obtained. The obtained cumulative amount of hydrogen is regarded as the amount of diffusible hydrogen.
[0081] [Manufacturing method] An example of a method for manufacturing the nitrided steel part of this embodiment will be described below. Note that the nitrided steel part of this embodiment is not limited to the manufacturing method described below.
[0082] The manufacturing method of the nitrided steel part of this embodiment includes a step of preparing a steel material (steel material preparation step) and a step of manufacturing the nitrided steel part from the steel material (nitrided steel part manufacturing step). Each step will be described in detail below.
[0083] [Steel preparation process] In the steel material preparation step, a steel material that will be the raw material for the nitriding steel part is prepared. The steel material that will be the raw material for the nitriding steel part of this embodiment has the following configuration.
[0084] [Chemical composition and microstructure of steel materials used for nitrided steel parts] The range of content of each element in the chemical composition of the steel material that is the raw material for the nitrided steel part of this embodiment is the same as the range of content of each element in the chemical composition of the core of the nitrided steel part. That is, the chemical composition of the steel is, in mass%, C: 0.03 to 0.25%, Si: 0.02 to 0.50%, Mn: over 0.70 to 2.50%, P: 0.035% or less, S: 0.050% or less, Al: 0.005 to 0.050%, Cr: 0.03 to less than 0.30%, V: over 0.10 to 0.40%, N: 0.003 to 0.030%, Nb: 0 to 0.100%, B: 0 to 0.0100%, Cu: 0 to 0.20%, Ni: 0 to 0.20%, Ca: 0 to 0.0050%, Bi: 0 to 0.100%, Pb: 0 to 0.090%, Mo: 0 to 0.05%, Ti: 0 to 0.005%, and the balance being Fe and impurities. The microstructure in the steel material from which the nitrided steel part of this embodiment is made is the same as that of the nitrided steel part described above.
[0085] [V in precipitates] / [V] of steel material used for nitrided steel parts] Further, when the V in the chemical composition of the steel material that is the raw material for the nitriding steel part of this embodiment is defined as [V] (mass%) and the total content of V in V precipitates in the steel material is defined as "V in precipitates" (mass%), [V in precipitates] / [V] is 0.05 to less than 0.30.
[0086] In the steel material for the nitrided steel part of this embodiment, if [V in precipitates] / [V] is less than 0.05 to 0.30, a sufficient amount of plate-shaped V precipitates will precipitate in the nitriding treatment process described below, resulting in increased bending fatigue strength of the nitrided steel part of this embodiment.
[0087] The steel material that is the raw material for the nitriding steel part of this embodiment may be supplied by a third party or may be manufactured. When manufacturing a steel material, the steel material preparation process includes a process of preparing a raw material (raw material preparation process) and a process of hot working the raw material to manufacture the steel material (hot working process).
[0088] [Material preparation process] Molten steel having the above-mentioned chemical composition is produced. A material is prepared using the molten steel. For example, the molten steel having the above-mentioned chemical composition is produced using a converter, an electric furnace, or the like. A slab is produced using the molten steel by a continuous casting method. Alternatively, an ingot is produced using the molten steel by an ingot casting method.
[0089] [Hot processing process] A prepared material is subjected to hot working to produce a steel material. When hot rolling is performed as hot working, for example, the following method is available. Hot rolling includes a rough rolling process in which the material is roughly rolled to produce a billet, and a finish rolling process in which the billet is finish rolled to produce a steel material. The rough rolling process, for example, includes the following steps: After heating the material (slab, ingot), it is bloomed using a blooming mill. If necessary, after blooming, the material is further rolled in a continuous rolling mill to produce a billet. In the continuous rolling mill, horizontal roll stands and vertical roll stands are alternately arranged in a row, and the material is rolled into a billet using grooves formed in the rolling rolls of each stand. It is to be noted that billets may be directly produced by a continuous casting method.
[0090] The finish rolling process, for example, involves the following steps: The billet produced in the rough rolling process is charged into a heating furnace and heated. The heated billet is then finish rolled (hot rolled) in a finishing rolling mill train to produce a bar and wire of a predetermined diameter. The finishing rolling mill train includes a plurality of stands arranged in a line. Each stand includes a plurality of rolls arranged around a pass line. The billet is rolled using grooves formed in the rolling rolls of each stand to produce a steel material (bar and wire).
[0091] The hot working step is not limited to hot rolling. In the hot working step, hot forging or hot extrusion may be performed instead of the above-mentioned hot rolling.
[0092] [About heating temperature] In the hot working process, the heating temperature of the steel material immediately before the final hot working is performed is, for example, 1000 to 1300° C. For example, when the hot working process includes a rough rolling process and a finish rolling process, the heating temperature in the heating furnace in the finish rolling process is 1000 to 1300° C. If the heating temperature in the heating furnace in the finish rolling process is 1000 to 1300° C., V precipitates generated before the hot working process will be sufficiently dissolved, provided that other manufacturing conditions are satisfied.
[0093] [Finishing temperature] In the hot working process, the temperature of the steel material after the final reduction is defined as the finishing temperature (°C). When the hot working process includes a rough rolling process and a finish rolling process, the finishing temperature means the temperature of the steel material (surface temperature of the steel material) at the outlet side of the stand that performed the final reduction in the finishing rolling mill train in the finish rolling process. The finishing temperature is, for example, 800 to 1200°C. If the finishing temperature is 800 to 1200°C, reprecipitation of V that has been dissolved in the heating furnace can be sufficiently suppressed, provided that other manufacturing conditions are satisfied.
[0094] [Cooling rate] In the hot working step, the cooling rate after hot working is, for example, 0.4 to 4.0°C / s. Here, the cooling rate after hot working is defined as follows. After completion of hot working, the average cooling rate at which the steel material temperature reaches 200°C from the finishing temperature is defined as the cooling rate after hot working (°C / s). If the cooling rate after hot working is 0.4 to 4.0°C / s, the ferrite area ratio in the steel material is 20 to 90%, and further, [V in precipitates] / [V] in the steel material is 0.05 to less than 0.30, provided that other manufacturing conditions are satisfied.
[0095] The steel material is manufactured by the above manufacturing method. As mentioned above, the manufacturing method of the steel material is not limited to this example, and the steel material to be used as the raw material for the nitrided steel parts may be manufactured by other manufacturing methods.
[0096] [Other processes] The steel material after the hot working process may be subjected to a normalizing treatment in order to adjust the microstructure.
[0097] [Normalizing process] The normalizing treatment step is an optional step and may not be performed. If performed, the heat treatment temperature in the normalizing treatment may be 1000 to 1300°C, and the cooling rate after holding at the heat treatment temperature may be 0.4 to 4.0°C / s. In other words, the heat treatment temperature and cooling rate in the normalizing treatment are in the same range as the heating temperature and cooling rate in the hot working step.
[0098] [Manufacturing process for nitriding steel parts] An example of a method for manufacturing a nitrided steel part using the above-mentioned steel material will be described. The manufacturing process for a nitrided steel part includes a step of cold working the steel material (cold working step) and a step of nitriding the cold worked steel material (nitriding step). If necessary, a step of cutting the cold worked steel material (cutting step) may be further included before the nitriding step. Each step will be described below.
[0099] [Cold working process] The cold working process includes a process of drawing the steel material (drawing process) and a process of upsetting the steel material after the drawing process (upsetting process). The drawing process involves wire drawing. The wire drawing may involve only primary wire drawing, or multiple drawing processes such as secondary wire drawing may be performed. After the drawing process, the steel material may be cut to an appropriate length depending on the nitrided steel part to be manufactured. Hereinafter, the steel material after the drawing process, or the steel material after the drawing process and cutting to an appropriate length is referred to as an intermediate product. The upsetting process involves upsetting, which compresses the intermediate product in the length direction. The upsetting process may involve only one upsetting step, or multiple upsetting steps.
[0100] In the drawing and upsetting processes, the steel material is subjected to loads in two directions, the direction perpendicular to the length of the steel material and the length of the steel material. The loads applied from two directions cause the direction of movement of dislocations in the crystal grains of the steel material to be inconsistent. This makes cross slip more likely to occur. When cross slip occurs, dislocations are more likely to collide with each other. This increases the number of dislocations that collide and cannot move, and the number of dislocations that are left behind in the crystal grains increases. This increases the dislocation density in the crystal grains. If the dislocation density increases, strain is formed. In the nitriding process described below, V precipitates are more likely to precipitate in the parts where strain is formed in order to eliminate the formed strain. If V precipitates precipitate, the bending fatigue strength of the manufactured nitrided steel parts is improved by precipitation strengthening.
[0101] That is, there is a positive correlation between the amount of strain formed in the steel material and the amount of V precipitates. In the nitrided steel part according to this embodiment, strain is generated by performing two-way cold working by drawing and upsetting. Hereinafter, the strain generated by the cold working process is referred to as cold working strain. V precipitates are precipitated in the nitriding process described below. By performing the nitriding process described below under appropriate conditions, plate-shaped V precipitates can be precipitated. That is, there is a positive correlation between the amount of cold working strain (hereinafter also referred to as cold working strain amount) and the amount of plate-shaped V precipitates.
[0102] The cold working strain is the sum of the amount of strain caused by the drawing process (drawing strain) and the amount of strain caused by the upsetting process (upsetting strain). The drawing strain and upsetting strain are calculated using the true strain ε (%) by cylindrical approximation defined by formula (2). ε(%)=|ln{1+(L-L0) / L0}|×100 (2) Here, when calculating the amount of drawing strain, L is the length in the wiredrawing direction of the steel material after the drawing process, and L0 is the length in the wiredrawing direction of the steel material before the drawing process. When calculating the amount of upsetting strain, L is the length in the wiredrawing direction of the intermediate product after the upsetting process, and L0 is the length in the wiredrawing direction of the intermediate product before the upsetting process.
[0103] The cold working strain is 20% or more. If the cold working strain is 20% or more, the dislocation density in the steel increases. Therefore, in the nitriding process described later, plate-shaped V precipitates are easily formed. As a result, the bending fatigue strength of the nitrided steel part is improved. The preferable lower limit of the cold working strain is 30%, more preferably 35%. If the cold working strain is less than 20%, the above-mentioned effect cannot be sufficiently obtained. On the other hand, the upper limit of the cold working strain is not particularly limited, but is preferably 150% or less. If the cold working strain exceeds 150%, the working pressure during the cold working process becomes too high. In other words, the deformation resistance of the intermediate product after the cold working process becomes too high. Therefore, the steel becomes more likely to crack during cold working. Therefore, the preferable upper limit of the cold working strain is 120%, more preferably 80%.
[0104] As described above, the nitriding steel part according to the present embodiment improves bending fatigue strength by carrying out the drawing process and the upsetting process. Therefore, the lower limit of the drawing strain caused by the drawing process is more than 5%, and the lower limit of the upsetting strain caused by the upsetting process is more than 5%. When at least one of the drawing strain and the upsetting strain is 5% or less, plate-shaped V precipitates are not obtained sufficiently. As a result, bending fatigue strength is not obtained sufficiently. The upper limits of the drawing strain and the upsetting strain are not particularly limited. A preferable upper limit of the drawing strain is, for example, 40%, and more preferably 30%. A preferable upper limit of the upsetting strain is, for example, 80%, and more preferably 50%.
[0105] [Nitriding process] The cold-worked product is subjected to a nitriding process, in which the treatment temperature (°C) and the holding time (min) at the treatment temperature are as follows:
[0106] Processing temperature: 500℃~700℃ The treatment temperature of the nitriding process (hereinafter also referred to as the nitriding temperature) is generally set according to conditions such as the required thickness of the nitrided layer. However, in the present invention, in order to precipitate plate-shaped V precipitates in the cold-worked structure of the parent phase during nitriding, it is necessary to limit the nitriding temperature. If the nitriding temperature is 500°C or higher, a sufficient nitrided layer is formed on the surface layer of the nitrided steel part, and sufficient plate-shaped V precipitates are precipitated in the core of the nitrided steel part. As a result, the bending fatigue strength of the nitrided steel part is improved. If the nitriding temperature is less than 500°C, a sufficient nitrided layer is not formed on the surface layer of the nitrided steel part, and sufficient plate-shaped V precipitates are not precipitated in the core of the nitrided steel part. On the other hand, if the nitriding temperature is more than 700°C, the nitrides in the nitrided layer are coarsened in the surface layer of the nitrided steel part, resulting in insufficient hardness of the nitrided layer. If the nitriding temperature is more than 700°C, the change from plate-shaped V precipitates to spherical V precipitates is promoted in the core of the nitrided steel part. Therefore, plate-shaped V precipitates are not sufficiently precipitated in the core of the nitrided steel part. As a result, the bending fatigue strength is not sufficiently increased. Therefore, the nitriding temperature is 500°C to 700°C. If the nitriding temperature is 500°C to 700°C, high bending fatigue strength can be obtained.
[0107] Holding time: 60~300 minutes The holding time at the above nitriding temperature is set to 60 to 300 minutes. If the holding time is 60 to 300 minutes, a sufficient nitride layer is formed on the surface layer of the nitrided steel part, and sufficient plate-shaped V precipitates are precipitated in the core of the nitrided steel part. As a result, high bending fatigue strength is obtained. If the holding time is less than 60 minutes, a sufficient nitride layer is not formed on the surface layer of the nitrided steel part, and bending fatigue strength is not sufficiently increased. On the other hand, if the holding time is more than 300 minutes, the change from plate-shaped V precipitates to spherical V precipitates is promoted in the core of the nitrided steel part. Therefore, plate-shaped V precipitates are not sufficiently precipitated in the core of the nitrided steel part. As a result, bending fatigue strength is not sufficiently increased. Therefore, the holding time is 60 to 300 minutes. The preferable lower limit of the holding time is 75 minutes, more preferably 90 minutes. The preferable upper limit of the holding time is 240 minutes, more preferably 180 minutes.
[0108] The nitriding method in the present invention is not particularly limited. Any of gas nitriding, gas soft nitriding, salt bath nitriding, and salt bath soft nitriding may be used. However, plasma nitriding that does not satisfy the above nitriding temperature is inappropriate.
[0109] [Cutting process] The intermediate product after the cold working step is cut as necessary before the nitriding step to produce a nitrided steel part. The produced nitrided steel part has high bending fatigue strength due to the nitriding step. The nitrided steel part according to the present invention can be produced by the above-mentioned production steps (cold working step-cutting step-nitriding step, or cold working step-nitriding step) instead of the conventional production steps (hot forging step-cutting step). This makes it possible to increase productivity.
[0110] As described above, the nitrided steel part according to the present invention has high bending fatigue strength.
[0111] The present invention will now be described in more detail with reference to examples. EXAMPLES
[0112] Various nitrided steel parts were manufactured and evaluated for bending fatigue strength.
[0113] Molten steels with test numbers 1 to 68 having the chemical compositions shown in Tables 1 and 2 were produced by vacuum melting. Ingots weighing 150 kg were produced using the molten steels. A blank in the "Chemical Composition" column in Tables 1 and 2 means that the content of the corresponding element was below the detection limit.
[0114] [Table 1]
[0115] [Table 2]
[0116] In addition, when the measured value of the Mo content in the impurities is less than 0.01%, and when the measured value of the Ti content is less than 0.001%, the value is indicated as "-" from the viewpoint that the performance is equivalent to that of no content.
[0117] The produced ingots were subjected to hot forging simulating hot working to produce forged and stretched round bars with a diameter of 24 mm (φ24). The heating temperature in the hot forging was 1200°C, and the finishing temperature was 1000°C. The cooling rate after hot forging was 0.5°C / s. The forged and stretched round bars were produced by the above method. For test number 66, the heating temperature and finishing temperature conditions were as described above, and hot forging was performed under the cooling rate after hot forging: 0.1°C / s. For test numbers 67 and 68, the heating temperature and finishing temperature conditions were as described above, and hot forging was performed under the cooling rate after hot forging: 10.0°C / s.
[0118] The produced round bar forged and stretched material was subjected to cold working simulating a cold working process, and then a nitriding process was performed to produce a nitrided steel part. In the cold working process, a drawing process was performed on the round bar forged and stretched material of each test number, and then an upsetting process was performed. The drawing strain amount (%) and the upsetting strain amount (%) in the drawing process and the upsetting process were as shown in Tables 1 and 2. The nitriding process was performed on the round bar forged and stretched material after the cold working process. In the nitriding process, the treatment temperature (°C) and the holding time (min) were as shown in Tables 1 and 2. In the Ono type rotating bending fatigue test described later, the steel material after the cold working was cut, and an Ono type rotating bending fatigue test piece having the shape shown in FIG. 1 was obtained. Then, a nitriding process was performed under the conditions shown in Tables 1 and 2 to produce a nitrided steel fatigue test piece. The nitrided steel part and the nitrided steel fatigue test piece were produced by the above method.
[0119] [Microstructure observation] Test pieces were taken from the center of the forged and drawn round bar of each test number. The center means the part including the central axis of the forged and drawn round bar. The surface perpendicular to the rolling direction of the forged and drawn round bar was used as the observation surface. The observation surface was mechanically polished and corroded with 3% nital (ethanol + 3% nitric acid solution). The corroded observation surface was observed at the R / 2 position (center position of radius R) of the forged and drawn round bar with an optical microscope. The observation magnification was 400 times, and the observation field was 5 fields. The area ratio (%) of pro-eutectoid ferrite and the total area ratio (%) of pearlite and bainite were obtained for each field. The average value of the 5 fields was calculated for each structure, and the ferrite area ratio (%) and the total area ratio (%) of pearlite and bainite of the forged and drawn round bar of each test number were obtained.
[0120] The microstructure of the nitrided steel parts of each test number was observed in the same manner as for the round bar forged and drawn material. Specifically, the L-section of the nitrided steel parts (a section parallel to the direction of progress in the drawing process of the cold working process described later) was used as the observation surface. The observation surface was mechanically polished and corroded with 3% nital (ethanol + 3% nitric acid solution). Of the corroded observation surface, a position 5 mm from the surface of the nitrided steel parts was observed with an optical microscope. The observation magnification was 400 times, and the observation field was 5 fields. The area ratio (%) of pro-eutectoid ferrite and the total area ratio (%) of pearlite and bainite were obtained for each field. The average value of the 5 fields for each structure was calculated, and it was determined as the ferrite area ratio (%) and the total area ratio (%) of pearlite and bainite of the nitrided steel parts of each test number. The ferrite area ratio (%) and the total area ratio (%) of pearlite and bainite of the obtained nitrided steel parts are shown in Tables 1 and 2.
[0121] "F% (%)" in "nitrided steel parts" in Tables 1 and 2 means the area ratio (%) of ferrite in the microstructure of the observed nitrided steel parts. "P+B% (%)" in "nitrided steel parts" in Tables 1 and 2 means the total area ratio (%) of pearlite and bainite in the microstructure of the observed nitrided steel parts.
[0122] [Measurement of total V content in V precipitates ([V in precipitates])] A 10 mm cube of extraction residue test piece was taken from the core of each nitrided steel part with each test number. The total V content (mass%) in the V precipitates due to the extraction residue was determined using the extraction residue test piece by the method described above.
[0123] [Ono type rotating bending fatigue test] Using the nitrided steel fatigue test pieces of each test number, the Ono-type rotating bending fatigue test was carried out in the air at room temperature. The rotation speed was set at 3000 rpm, and the number of repeated stress loads was set at 10. 7 The maximum stress at which the specimen did not break after the cycles was taken as the bending fatigue strength (MPa). The bending fatigue strengths obtained are shown in the "Fatigue strength (MPa)" column of Tables 1 and 2. When the bending fatigue strength was 650 MPa or more, the bending fatigue strength was judged to be high. On the other hand, when the bending fatigue strength was less than 650 MPa, the bending fatigue strength was judged to be low.
[0124] [Measurement of diffusible hydrogen content] Test pieces for measuring the amount of diffusible hydrogen were prepared. A round bar with a diameter of 7 mm and a length of 40 mm was cut out from the core of each nitrided steel part with each test number. Specifically, the round bar was cut out by cutting to a depth of 5 mm or more from the surface of the nitrided steel part. The cut out round bar was used as a test piece for measuring the amount of diffusible hydrogen. The amount of diffusible hydrogen was measured for the test pieces for measuring the amount of diffusible hydrogen prepared by the above method. The results are shown in Tables 1 and 2. When the amount of diffusible hydrogen was 0.10 ppm or more, it was determined that the amount of diffusible hydrogen was sufficient and that the plate-shaped V precipitates were sufficiently precipitated. On the other hand, when the amount of diffusible hydrogen was less than 0.10 ppm, it was determined that the amount of diffusible hydrogen was insufficient and that the precipitation of the plate-shaped V precipitates was insufficient.
[0125] [Test Results] The test results are shown in Tables 1 and 2. The area ratios of the microstructures of the forged and drawn round bar materials of each test number except for test numbers 60 and 61 were the same as the area ratios of the nitrided steel parts of each test number. In the structure of the forged and drawn round bar material of test number 60, the area ratio of ferrite was 70%, and the total area ratio of pearlite and bainite was 30%. In the structure of the forged and drawn round bar material of test number 61, the area ratio of ferrite was 58%, and the total area ratio of pearlite and bainite was 42%.
[0126] With reference to Tables 1 and 2, the nitrided steel parts of test numbers 1 to 40 had appropriate chemical compositions in the core and satisfied formula (1). Furthermore, the conditions of the cold working process and the nitriding treatment process were appropriate for the nitrided steel parts of test numbers 1 to 40. Therefore, the area ratio of ferrite in the microstructure of the nitrided steel parts of test numbers 1 to 40 was 20 to 90%. Furthermore, the nitrided steel parts of test numbers 1 to 40 satisfied formula (1) and had a diffusible hydrogen amount of 0.10 ppm or more. Therefore, the bending fatigue strength of the nitrided steel parts of test numbers 1 to 40 was 650 MPa or more, and was high.
[0127] On the other hand, in test number 41, the C content was too high, and as a result, the cold workability of the forged and drawn round bar was poor.
[0128] In test number 42, the C content was too low. Therefore, the ferrite area ratio of the nitrided steel part was too high. Therefore, the plate-shaped V precipitates were not precipitated sufficiently. As a result, the formula (1) was not satisfied, the amount of diffusible hydrogen was less than 0.10 ppm, and the bending fatigue strength was less than 650 MPa.
[0129] Test No. 43 had too low a Si content, and therefore had a bending fatigue strength of less than 650 MPa.
[0130] Test No. 44 had too high a Si content, which resulted in poor cold workability of the forged and drawn round bar.
[0131] Test No. 45 had too high a Mn content, which resulted in poor cold workability of the forged and drawn round bar.
[0132] Test No. 46 had an excessively high Mn content. Therefore, the area ratio of ferrite in the forged and drawn round bar was less than 20%. As a result, the cold workability of the forged and drawn round bar was poor.
[0133] Test No. 47 had too high a V content, which resulted in poor cold workability of the forged round bar.
[0134] In test number 48, the V content was too low, so V precipitates were not sufficiently formed, and as a result, formula (1) was not satisfied, the amount of diffusible hydrogen was less than 0.10 ppm, and the bending fatigue strength was less than 650 MPa.
[0135] Test No. 49 had too high a Cr content, which resulted in a bending fatigue strength of less than 650 MPa.
[0136] Test No. 50 had too high N content. Therefore, before the cold working process, excessive V nitrides were precipitated during cooling after hot working. Therefore, plate-shaped V precipitates were not precipitated sufficiently in the nitriding process. As a result, the amount of diffusible hydrogen was less than 0.10 ppm, and the bending fatigue strength was less than 650 MPa.
[0137] Test No. 51 had too high a Ti content, which resulted in poor cold workability of the forged round bar.
[0138] Test No. 52 had too high a Mo content, which resulted in poor cold workability of the forged round bar.
[0139] In the test numbers 53 and 54, the cold working strain in the cold working process was too low. Therefore, plate-shaped V precipitates were not sufficiently precipitated. As a result, the formula (1) was not satisfied, the amount of diffusible hydrogen was less than 0.10 ppm, and the bending fatigue strength was less than 650 MPa.
[0140] In the test numbers 55 and 56, the upsetting process was not performed in the cold working process. Therefore, plate-shaped V precipitates were not sufficiently precipitated. As a result, the amount of diffusible hydrogen was less than 0.10 ppm, and the bending fatigue strength was less than 650 MPa.
[0141] In the test numbers 57 and 58, the drawing process was not performed in the cold working process. Therefore, plate-shaped V precipitates were not sufficiently precipitated. As a result, the amount of diffusible hydrogen was less than 0.10 ppm, and the bending fatigue strength was less than 650 MPa.
[0142] In test number 59, the nitriding temperature was too low, so V precipitates were not sufficiently formed, and as a result, formula (1) was not satisfied, the amount of diffusible hydrogen was less than 0.10 ppm, and the bending fatigue strength was less than 650 MPa.
[0143] In the test pieces 60 and 61, the nitriding temperature was too high. Therefore, the plate-shaped V precipitates were not sufficiently precipitated in the cooling process after the nitriding. As a result, the amount of diffusible hydrogen was less than 0.10 ppm, and the bending fatigue strength was less than 650 MPa.
[0144] In test number 62, the holding time at the nitriding temperature was too short, so that the plate-shaped V precipitates were not sufficiently precipitated, and as a result, the formula (1) was not satisfied, the amount of diffusible hydrogen was less than 0.10 ppm, and the bending fatigue strength was less than 650 MPa.
[0145] In test numbers 63 to 65, the holding time at the nitriding temperature was too long, so that the plate-like V precipitates were not precipitated sufficiently, and as a result, the amount of diffusible hydrogen was less than 0.10 ppm, and the bending fatigue strength was less than 650 MPa.
[0146] In test number 66, although the chemical composition of the core was appropriate, the cooling conditions in the hot working process in the manufacture of the forged and drawn round bar material were not appropriate. As a result, the [V in precipitates] / [V] of the forged and drawn round bar material was 0.30 or more. As a result, the amount of diffusible hydrogen was less than 0.10 ppm. Furthermore, in the microstructure of the forged and drawn round bar material, the area ratio of ferrite was more than 90%. As a result, in the microstructure of the nitrided steel part, the area ratio of ferrite was more than 90%. As a result, the bending fatigue strength was less than 650 MPa.
[0147] In test numbers 67 and 68, although the chemical composition of the core was appropriate, the cooling conditions in the hot working process in the manufacture of the forged and drawn round bar material were not appropriate. Therefore, the area ratio of ferrite in the microstructure of the forged and drawn round bar material was less than 20%. As a result, the cold workability of the forged and drawn round bar material was poor.
[0148] The embodiments of the present disclosure have been described above. However, the above-described embodiments are merely examples for implementing the present disclosure. Therefore, the present disclosure is not limited to the above-described embodiments, and can be implemented by appropriately modifying the above-described embodiments without departing from the spirit of the present disclosure.
Claims
1. 1. A nitrided steel part, comprising: a nitrided layer on the surface layer of the nitrided steel part; A core portion located inside the nitride layer, The chemical composition of the core is, in mass%, C: 0.03-0.25%, Si: 0.02-0.50%, Mn: more than 0.70 to 2.50%, P: 0.035% or less, S: 0.050% or less, Al: 0.005-0.050%, Cr: 0.03 to less than 0.30%; V: more than 0.10 to 0.40%, N: 0.003-0.030%, Nb: 0 to 0.100%, B: 0 to 0.0100%, Cu: 0 to 0.20%, Ni: 0 to 0.20%, Ca: 0-0.0050%, Bi: 0-0.100%, Pb: 0 to 0.090%, Mo: 0 to 0.05%, and Ti: 0 to 0.005%; The balance is Fe and impurities, When the V content in the chemical composition of the core portion is defined as [V] (mass%) and the total V content in the V precipitates of the core portion is defined as [V in precipitates] (mass%), formula (1) is satisfied, The amount of diffusible hydrogen is 0.10 ppm or more when hydrogen is charged in a 3% NaCl-3 g / LNH 4 SCN aqueous solution by a cathodic hydrogen charging method in which the current density is 0.1 mA / cm 2 and the current application time is 72 hours. Nitrided steel parts. [V in precipitate] / [V]≧0.30 (1)
2. 2. The nitrided steel component according to claim 1, The chemical composition of the core portion further includes, instead of a part of Fe, Nb: 0.001 to 0.100%, and B: 0.0001 to 0.0100%, Contains one or more selected from the group consisting of Nitrided steel parts.
3. 3. The nitriding steel part according to claim 1 or 2, The chemical composition of the core portion further includes, instead of a part of Fe, Cu: 0.01 to 0.20%, and Ni: 0.01 to 0.20%, Contains one or more selected from the group consisting of Nitrided steel parts.
4. A nitriding steel part according to any one of claims 1 to 3, The chemical composition of the core portion further includes, instead of a part of Fe, Ca: 0.0001-0.0050%, Bi: 0.001 to 0.100%, and Pb: 0.001-0.090%, Contains one or more selected from the group consisting of Nitrided steel parts.
5. A nitriding steel part according to any one of claims 1 to 4, The chemical composition of the core portion further includes, instead of a part of Fe, Mo: 0.01 to 0.05%, and Ti: 0.001 to 0.005%, Contains one or more selected from the group consisting of Nitrided steel parts.
Citation Information
Patent Citations
Steel for soft-nitriding excellent in cold forgeability
JP1997279296A
Steel material for carburization processing
JP2019049032A
Steel material for cold forging
JP2019173168A
Method for manufacturing nitrided component and steel for nitriding
WO2016098143A1
Reinforcing bar for nitriding, and machine component
WO2020003425A1